2010
DOI: 10.1037/a0017942
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress, well-being, and legal recognition in same-sex couple relationships.

Abstract: Legal recognition of same-sex couple relationships provides at least some material benefits to couple members; however, few studies have examined the associations between legal recognition and psychological distress or well-being. Using an online survey sample of 2,677 lesbian, gay, bisexual (LGB) individuals, participants were placed in 4 groups: single, dating, in a committed relationship, and in a legally recognized relationship. Analyses revealed that participants in committed or legally recognized relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
124
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 201 publications
(147 citation statements)
references
References 14 publications
13
124
0
4
Order By: Relevance
“…In the same study, those who were married also had higher odds of having positive affect or good mood (Wight et al, 2012). One of the few studies on same-sex relationships with a large national-level U.S. sample of over 2,000 respondents found that married individuals reported reduced levels of stress, depressive symptoms and internalized homophobia and reported a higher sense of meaning of life compared to those who were in non-marital committed relationships (Riggle et al, 2010). This was the only study to date to our knowledge that compared those who are married to those who are in committed relationships whereas most studies compare married individuals to those who are single.…”
Section: Marital Benefits and Same-sex Marriagementioning
confidence: 85%
See 4 more Smart Citations
“…In the same study, those who were married also had higher odds of having positive affect or good mood (Wight et al, 2012). One of the few studies on same-sex relationships with a large national-level U.S. sample of over 2,000 respondents found that married individuals reported reduced levels of stress, depressive symptoms and internalized homophobia and reported a higher sense of meaning of life compared to those who were in non-marital committed relationships (Riggle et al, 2010). This was the only study to date to our knowledge that compared those who are married to those who are in committed relationships whereas most studies compare married individuals to those who are single.…”
Section: Marital Benefits and Same-sex Marriagementioning
confidence: 85%
“…Thus, it is important to understand whether benefits and protections stemming from marriage are being realized for this population. Due to the recent legalization of same-sex marriage, there is limited, but a steadily growing number, of studies that have examined its effect on the lives of LGBT people (Bariola et al, 2015;Wight et al, 2013;Riggle et al, 2010;Dee, 2008;Mathy et al, 2003). Some studies have shown that relationships benefit partners in same-sex dyads.…”
Section: Marital Benefits and Same-sex Marriagementioning
confidence: 99%
See 3 more Smart Citations